If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2f + -4) = -4(-5 + 2) Reorder the terms: -2(-4 + 2f) = -4(-5 + 2) (-4 * -2 + 2f * -2) = -4(-5 + 2) (8 + -4f) = -4(-5 + 2) Combine like terms: -5 + 2 = -3 8 + -4f = -4(-3) Multiply -4 * -3 8 + -4f = 12 Solving 8 + -4f = 12 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -4f = 12 + -8 Combine like terms: 8 + -8 = 0 0 + -4f = 12 + -8 -4f = 12 + -8 Combine like terms: 12 + -8 = 4 -4f = 4 Divide each side by '-4'. f = -1 Simplifying f = -1
| -7+6y+y^2=0 | | -3(a+6)=22 | | 5x(9-x)=37.5 | | 3(4y-5)= | | 26x+4=5(5x+4) | | -2x+1=-7 | | 4y-49=0 | | 8y+11=6y-3 | | x+7=(8*x)+30 | | 6x+3=8x^2+4x | | -6-1=(-4)+15-1-5-2-1 | | 7x-5=8x+7 | | 4+3(2y-6)-3(4y+8)-10= | | 4+3(2y-6)-3(4y+8)-10=-8 | | 3x+4=-14 | | 59-3x=6x+15 | | -2(n+3)=-24 | | 2x+10+2x-6=40 | | 5(x+5)-7x=13 | | 5v-15=0 | | x^3+6x^2+12x+5=0 | | (3x+35)=4x | | x+(-8)=-3 | | 4(y-5)-7=-15 | | -8x+12x+4y-4y=-2-12 | | 5(x-3)=-(15+5x) | | -3(2x-5)-12=2x-25 | | 46-5=4x+17 | | .02x+.03x=.25 | | -5(3x-2)+x=0 | | 4(y-5)/7=-15 | | 1/2=1/2(t)+3 |